Synthesis of biomass-derived carbon aerogel/MnOx composite as electrode material for high-performance supercapacitors. (10th September 2021) - Zhou, Huiming; Zhan, Yinbo; Guo, Feiqiang; Du, Shilin; Tian, Beile; Dong, Yichen; Qian, Lin
Highlights: A strategy was developed to synthesize biomass (radish) derived carbon aerogel/MnO x composites. A cross-linked 3D carbon structure with uniform growth of MnO x was obtained. The highest gravimetric specific capacitance of 557 F/g was achieved at 1 A/g. The power density reached 4786.4 W/kg at an energy density of 248.2 Wh/kg. Abstract: Synthesis of economical and high-performance carbon materials from biomass has been seen as an emerging strategy for energy storage devices. In this work, using radish as the raw material, a facile method for the synthesis of 3D carbon aerogels incorporated with MnO x nanoparticles has been developed. At a suitable impregnation amount of Mn(NO3 )2, MnO x nanoparticles with a diameter of around 110 nm grow uniformly on the surface of the carbon aerogel, during which ordered carbon structures can be formed and results in an increase in the graphitization degree. The cross-linked 3D dimensional carbon structure and uniform growth of MnO x nanoparticles are beneficial to the electrochemical performance of the carbon aerogel/MnO x composite as electrode materials in supercapacitor applications. The carbon aerogel/MnO x composite impregnated with 1.6 mmol Mn(NO3 )2 and activated under CO2 atmosphere (CAC@MnO x -1.6) reached the highest gravimetric specific capacitance of 557 F g −1 at a current density of 1 A g −1 in the three-electrode system using 2 M KOH as the electrolyte. In a two-electrode system, a high gravimetric specific capacitance of 447 F g −1 was obtained using the CAC@MnO x -1.6-based electrode, and the power density reached 4786.44 W kg −1 at an energy density of 248.23 Wh kg −1 with a current density of 1 A g −1 in the voltage range of -1 1 V. Graphical abstract: Image, graphical abstract